Selection attributes of innovative digital platform-based subscription services: A case of South Korea - Yoojin Kim; Bo-Young Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study aimed to make an empirical analysis of the effects that the selection attributes of subscription services have on purchase intentions and continuous use intentions, based on the perceived value of digital platform-based subscription service users as a medium. A survey was conducted among 434 subscription service users in Korea, with content superiority, system quality, and service differentiation defined as key selection attributes based on a literature review. Upon analysis, content superiority and service differentiation were found to have a positive effect on perceived value, which in turn positively affected purchase intentions and continuous use intentions, which is why the hypothesis was consequently adopted. Service differentiation was also found to positively affect purchase intentions and continuous use intentions using perceived value as a medium. In contrast, system quality was found to have no effect on perceived value, nor did it affect purchase intentions or continuous use intentions using perceived value as a medium, which is why the hypothesis was rejected. In conclusion, among factors impacting decision-making or buying behavior among users of recent digital platform-based subscription services, new, unique, and meaningful content superiority was found to have a bigger impact compared to system-related aspects based on technology usability.
Keywords: 650; content superiority; digital platform; selection attributes; service differentiation; subscription service; system quality